Antecedents and outcomes of employee engagement. - Hor, Guoyong. (2013)
The present study tests a model of drivers and personality antecedents of employee engagement, which is associated with positive organizational outcomes. Drivers of engagement refer to the psychological conditions of meaningfulness, safety and availability (Kahn, 1990). Personality was measured using the five 16PF global factors (Cattell, 1946). Employee engagement was measured in terms of one's psychological state (state engagement) and behaviors (behavioral engagement; Kahn, 1990). Outcomes of engagement included organizational commitment, organizational satisfaction, advocacy towards organization, and desire to stay. Three hundred and eight participants from a large government organization in Singapore participated in this study. Results of our study suggest that, in addition to psychological meaningfulness and psychological availability, self-control was able to predict employee engagement. Psychological safety, extraversion, anxiety, independence and tough-mindedness were not significant predictors of employee engagement. We also found that state and behavioral engagement can be summarized by a second-order factor model of engagement, which positively predicted positive organizational outcomes. Implications of our results, limitations of the present study and considerations for future research were discussed.